'Hiccups of the mind': psychotherapy with a young boy with obsessive-compulsive disorder. Issue 2 (3rd May 2020) - Thomas, Sayi
ABSTRACT: This paper presents a case study of a six-year-old boy who, unusually, had intensive psychoanalytic psychotherapy as a form of treatment for OCD. Obsessive-compulsive disorder (OCD) can be clinically diagnosed as a psychiatric condition from the age of four or five. The standard treatment for OCD in the NHS tends to be a combination of cognitive and behavioural therapies. This little boy suffered classic symptoms of OCD, which included repetitive intrusive thoughts, compulsions, and ritualistic behaviour. After just over two years of psychoanalytic treatment, his distressing symptoms were alleviated, and in the follow-up sixteen months later, the symptoms had not re-emerged. This paper highlights the psychoanalytic approach used in this case, focusing on the meanings and possible aetiology of paediatric OCD. Using the qualitative research approach of thematic analysis, three main themes that emerged in this work are discussed, by referring to clinical examples from the child's therapy. Based on the findings, I suggest that the contribution and maintenance of early onset OCD in this boy, to some extent camouflaged infantile relationship struggles, particularly in relation to oedipal difficulties. I will describe a 'turning point' in the therapy, to further illustrate my formulation, as well the demonstrating the complexity of the process of change in child psychotherapy, as evidenced in this case.